Pustular Pyoderma Gangrenosum with Ulcerative Colitis an Uncommonly Seen Association - Pradipsinh Parmar; Pooja Agarwal; Kalgi Baxi; Vikram Chaudhary; Raju Chaudhary (Nepal Journal of Dermatology, Venereology & Leprology)
We report a case of a 36-year-old female having ulcerative colitis who had multiple papulo-pustular lesions over trunk and face. She had received treatment as acne vulgaris but due to lack of satisfactory response, histopathological evaluation was done which was consistent with pustular pyoderma gangrenosum. The diagnosis of pustular pyoderma gangrenosum is often challenging as there is no defining diagnostic clinical, laboratory or histopathological feature. Thus a high index of suspicion is essential to diagnose this condition.